Asp.Net for beginners : the simple guide to learning Asp.Net web programming fast! ([Place of publication not identified] : [Name of publisher not identified])
This book contains proven steps and strategies on how to become a truly skilled and talented Asp.Net user. It will take you from the very basics of this programming method, to in depth views and examples of what it can do and what it has to offer you. If you are ready to learn how to apply the techniques of Asp.Net to your website or other online sites, then you have found the ideal guide to get started.
Introduction -- Chapter 1: What is Asp.Net? -- Chapter 2: Getting started with Asp.Net -- Chapter 3: Website building with Asp.Net -- Chapter 4: Security when using Asp.Net for your website -- Chapter 5: Cookies and Asp.Net -- Chapter 6: Asp.Net goes mobile
Keywords: WEB PROGRAMMING; ASP.NET (COMPUTER PROGRAM LANGUAGE)